Environmental awareness and plastic use behavior during the Covid-19 pandemic - H. Herdiansyah; Nuraeni . (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Plastic waste in Indonesia increased significantly during the Covid-19 pandemic. With this surge in plastic consumption and waste, awareness of environmental sanitation becomes essential, especially regarding the use of plastic. Society must consider the impact of single-use plastics and implement good plastic waste management. This study aimed to determine the environmental awareness of a community and what factors contributed to its plastic waste utilization activities during the Covid-19 pandemic.METHODS: The data collection in this study was conducted using a questionnaire with a cross-sectional analytical approach. The study was conducted in Makassar City, South Sulawesi, the largest city in Eastern Indonesia, and purposive sampling was used to determine selected respondents. Data analysis was carried out using chi-square to identify partial relationships and logistic regression to distinguish relationships simultaneously.FINDINGS: This study found that 53.2 percent of respondents frequently used plastic during the Covid-19 pandemic. Partial relationship analysis showed that general knowledge about waste and its impact was not significantly related to plastic use activities during the pandemic. Meanwhile, knowledge about plastic use during the pandemic, knowledge of protecting the environment, attitudes toward plastic use, attitudes toward waste management, behavior toward plastic use, and behavior regarding processing plastic waste were significantly related to plastic use activities during the Covid-19 pandemic, with respective test values of 0.000 each. Willingness to pay was also significantly related to plastic use activities during the pandemic, with a test value of 0.007. Simultaneous analysis showed that knowledge about plastic use during the pandemic was related to plastic use activities during the same time frame, with an odds ratio value of 0.398 and a negative relationship direction. Plastic waste-processing behavior was the most dominant factor influencing plastic use activities during the Covid-19 pandemic, with a test value of 0.000 and a positive relationship direction. Respondents who did not have good waste management behavior were 3.963 times more likely to use plastic frequently in their daily activities during the pandemic.CONCLUSION: The study results show the importance of increasing knowledge regarding plastic use and waste management. Good knowledge will intervene in attitudes that encourage good behavior. This study focuses on the relationship between plastic processing behavior and the intensity of plastic use during the Covid-19 pandemic. It emphasizes the need for intervention in the form of education about the importance of protecting the environment and providing facilities that enable people to implement good waste-processing behavior.